2018
DOI: 10.1002/mds.27506
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonism due to A53E α‐synuclein gene mutation: Clinical, genetic, epigenetic, and biochemical features

Abstract: Background SNCA mutations cause autosomal dominant parkinsonism and inform our understanding of the molecular underpinnings of synucleinopathies. The most recently identified mutation, p.Ala53Glu (A53E), has only been observed in Finland. The objectives of this study were to examine clinical, genetic, epigenetic, and biochemical features of the first family outside Finland with A53E. Methods We examined a Canadian family with parkinsonism because of A53E using haplotype and DNA methylation analyses. We assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…16 Furthermore, investigation of a PD family with the p.A53E mutation in α-synuclein showed that an earlier onset was accompanied by increased DNAm-age acceleration. 74 Of note, the association between DNAm-age measures and disease traits may depend on the selected DNAm clock. In a study of multiple sclerosis, accelerated phenotypic aging was observed using DNAm PhenoAge, whereas the measures of the Horvath or Hannum clock did not differ from chronological age, 51 which likely reflects the different aging mechanisms behind each DNAm clock.…”
Section: Studies Of Dnam Clocks In Neurodegenerative Diseasesmentioning
confidence: 99%
“…16 Furthermore, investigation of a PD family with the p.A53E mutation in α-synuclein showed that an earlier onset was accompanied by increased DNAm-age acceleration. 74 Of note, the association between DNAm-age measures and disease traits may depend on the selected DNAm clock. In a study of multiple sclerosis, accelerated phenotypic aging was observed using DNAm PhenoAge, whereas the measures of the Horvath or Hannum clock did not differ from chronological age, 51 which likely reflects the different aging mechanisms behind each DNAm clock.…”
Section: Studies Of Dnam Clocks In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Two types of mutations in the SNCA gene have been linked to autosomal dominant forms of PD, highlighting distinct mechanisms by which ␣-Syn aggregation can be triggered: (i) increased gene dosage and (ii) point mutations enhancing ␣-Syn aggregation propensity. The latter, including A30P [37], E46K [38], H50Q [39,40], G51D [41], and A53T [42], A53V [43], and A53E [44] (see Fig. 1), have been discovered by genetic screens in families with hereditary PD and directly influence ␣-Syn aggregation to different extents and via discrete pathways [45].…”
Section: Snca Mutations Reveal Unique Features Of ␣-Syn Toxicity and mentioning
confidence: 99%
“…SNCA is highly produced in many cells and constantly degraded through chaperone-mediated autophagy (39). This protein has been implicated in other lysosomal storage diseases (40) and is well-known in synucleinopathy related neurodegenerative diseases such as Parkinson disease (41,42). Importantly, the aggregation of pathological SNCA isoforms has been reported as toxic to cells (43)(44)(45), and the modulation of SNCA-signalling reverses lysosomal clustering (46), suggesting that SNCA may be an intriguing therapeutic target for FD (47).…”
Section: Snca Accumulates In Gla-deficient Podocytes and Is Resistant To Short-term Ertmentioning
confidence: 99%